Learning to forget : schooling and family life in New Haven's working class, 1870-1940 - Lassonde, Stephen (Yale University Press, 2005)
This book offers an insightful view of the complex relations between home and school in the working-class immigrant Italian community of New Haven, Connecticut. Through the lenses of history, sociology, and education, Learning to Forget presents a highly readable account of cross-generational experiences during the period from 1870 to 1940, chronicling one generation's suspicions toward public education and another's need to assimilate. Through careful research Lassonde finds that not all working class parents were enthusiastic supporters of education. Not only did the time and energy spent in school restrict children's potential financial contributions to the family, but attitudes that children encountered in school often ran counter to the family's traditional values. Legally mandated education and child labour laws eventually resolved these conflicts, but not without considerable reluctance and resistance. "As original and enlightening a piece of historical work as I have read in the field of education in many years." John Modell, Brown University